The Legal Protection for Young Domestic Workers in Ethiopia - Degu, Temesgen Abebe (Indonesian Journal of Law and Society, 2023)
As the saying goes, the child is the father of the man. We must properly bring up and protect our children today not least because in the future they will shoulder huge responsibility in taking charge of this country after replacing us. In many countries, especially developing ones like Ethiopia, children engage in different types of works for various reasons. Domestic work is one of such sector. Child (domestic) work is not prohibited if it is done by those above the minimum working age (14 years) under a condition that is not exploitative. The problem in Ethiopia, though, is that (child) domestic work is altogether excluded from legal protection (under the labour proclamation). Without formal regulation, child domestics are prone to exploitation by their employers. This kind of exploitation is a human rights violation in addition to being a serious development concern and gender equality challenge. This research aims at examining the adequacy of legal protection for young domestic workers under the Ethiopian legal system. To this end, the research employs a cross-sectional qualitative research design. Within this design, the research adopts a phenomenological methodology. The research concludes that there is inadequate legal protection for young domestic workers in Ethiopia beginning from formation of contract to terms of employment and working conditions.